Diversity index of argania spinosa l. Skeels plant formation in the algerian western sahara - Sarra, Ghalem; Reda, Kechairi; Faiçal , Hassani; Imene, Abdelli (Bangladesh Journal of Botany, 2024)
The argan (Argania spinosa) is a xerothermophilous tree, endemic in North-West Africa. In Algeria, it is found as wild in the northwest of the Hamada du Drâa of Tindouf (Algerian Western Sahara), where it is characterized by a great floristic diversity. Several indices were calculated in this study to have a better knowledge on the state of biological diversity of the argan tree ecosystem. It is characterized by a floristic richness composed of 123 taxa belonging to 38 families including the dominance of three major floristic families: Asteraceae, Brassicaceae and Amaranthaceae. Biologically, the study area is dominated by therophytic species. This therophytization is marked by a general invasion of annual species. The diversity index of Shannon-Weaver (4.42) associated with that of Pilou's equitability (0.843) are relatively high, which showed that the flora of the argan forest of Tindouf is highly diverse. The disturbance index is high (76%) which reflects a significant degree of disturbance of the plant formation and also a strong anthropozoic influence. Bangladesh J. Bot. 53(3): 447-457, 2024 (September)